2021
DOI: 10.3389/fpsyg.2021.781631
|View full text |Cite
|
Sign up to set email alerts
|

Emotionality vs. Other Biobehavioural Traits: A Look at Neurochemical Biomarkers for Their Differentiation

Abstract: This review highlights the differential contributions of multiple neurochemical systems to temperament traits related and those that are unrelated to emotionality, even though these systems have a significant overlap. The difference in neurochemical biomarkers of these traits is analysed from the perspective of the neurochemical model, Functional Ensemble of Temperament (FET) that uses multi-marker and constructivism principles. Special attention is given to a differential contribution of hypothalamic–pituitar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 220 publications
0
18
0
Order By: Relevance
“…The further that research in the neurochemistry of emotionality advances, the more that neurochemical systems are linked to emotional regulation ( 61 ). In fact, dysregulation in practically all neurochemical families, especially monoamines, hormones, neuropeptides, opioid receptors, and transcription factors, appears to contribute to PSD ( 62 ). There are two main theoretical views about the determinants of PSD.…”
Section: Monoamine Transmitters In the Treatment Of Psdmentioning
confidence: 99%
“…The further that research in the neurochemistry of emotionality advances, the more that neurochemical systems are linked to emotional regulation ( 61 ). In fact, dysregulation in practically all neurochemical families, especially monoamines, hormones, neuropeptides, opioid receptors, and transcription factors, appears to contribute to PSD ( 62 ). There are two main theoretical views about the determinants of PSD.…”
Section: Monoamine Transmitters In the Treatment Of Psdmentioning
confidence: 99%
“…Brain structures and specific synapses vary dramatically regarding the types of neurotransmitters and receptors used during their activities. These variations are not random but reflect the functionality of neurochemical systems in behavioural regulation (as reviewed earlier in [7,8,[11][12][13][14][15][16][17][18][19]. Moreover, temperaments and symptoms of psychopathology are based on the same neurochemical cycles, and the idea of a continuum between them was supported by neurochemical correlates of several temperament traits:neuroticism [20,21], low endurance [22], rigidity (as low plasticity) [23,24], impulsivity [25][26][27], emotional dispositions [16,28], (low) empathic processing [29,30], compromised probabilistic (thought) processing [31], sensation/risk seeking [32,33], and (low) sustained attention [34,35].…”
Section: A Need For International Cooperation For Analysis Of Neuroch...mentioning
confidence: 99%
“…Environmental SEP infrastructures involve not only societal and informational establishments but also physical factors, such as diets and climates. Modern gut psychiatry, endocrinology and neuroimmunology have demonstrated that gut microbiota [81][82][83][84]110], immune [111][112][113][114] and hormonal systems [18,115,116] and amount of sunlight [15,117,118] impact many aspects of behaviour, with emotional regulation as the most explicit example. For example, sunlight stimulates the release of hypothalamic orexins that regulate behavioural arousal [15].…”
Section: Tandc Specialized Extended Phenotypes (Behavioural Bubbles) ...mentioning
confidence: 99%
See 2 more Smart Citations